Exploring The Implementation of Participation Point System (PPS) Technique in Vocational High School Speaking Classroom - Sugiana, Dian; Ahmad, Yousef Bani; Kartini, Dedeh (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to explore the application of student participation point techniques in vocational high schools. Active participation of students in the learning process has an important role in improving their speaking skills. Therefore, the point participation technique is used as a method to encourage students to be more active in participating in teaching speaking in class. This study used a qualitative approach with a narrative inquiry design. Data was collected through class observations, interviews with teachers and students, as well as analysis of documents related to the curriculum and the application of point participation techniques. The research sample was carried out in a vocational high school located in Karawang and has implemented the participation point system technique.The results of the study show that the use of the participation point system has a positive impact on students' speaking abilities at the school. Students who are less active because of fear and embarrassment become motivated to participate in learning speaking so that their abilities improve in terms of mastery of vocabulary, grammar and pronunciation.Keywords: participation points, students, vocational high schools, learning strategies, active participation.